Pengembangan Infrastruktur Air Bersih Di Pesantren Hizbul Wathan Muhammadiyah Parangloe-Gowa : Langkah Praktis Untuk Perubahan Sosial - Nawang, Nurnawaty; Bahtiar, Abd. Rahman; Nanda, Abd. Rakhim (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
Pesantren Hisbul Wathan Muhammadiyah is one of the pesantren in the hills located in Belapuranga Gowa Regency. who face the challenge of limited access to clean water, uses rainwater and water from nearby rivers because the clean water supply has not been obtained from PDAM. The Community Service method used includes identification of needs, planning and design of water tanks, and clean water installations in accordance with the needs. The implementation phase involves the active participation until the construction is completed, training and counseling on the management and maintenance of facilities are carried out. The benefits of this service have succeeded in increasing access to clean water and the quality of life through the construction of water tanks and clean water installations, as well as training held, the community has become more independent in managing and utilizing groundwater sources properly and sustainably and can be adopted surrounding.